Une transition énergétique non consensuelle ? Définition du concept chez les acteurs en Martinique - François Ory (Bulletin de l’Association de Géographes Français)
The purpose of this article is to present how the lack of consensus on the concept of energy transition can be addressed in order to explain the actors’ strategies around renewable electricity generation projects. The study specifically addresses the definitions given by the actors of a French overseas territory, which are treated using a grid composed of 8 notions of energy transition. Taking three conflicting developments in renewable electricity generation as the case study, this article highlights how the positions of the actors toward these structures can be explained according to their interpretation of the energy transition. The results show that individuals take a stand for or against conflicting local projects because of a territorial and local vision of the concept of energy transition, relaying energy-climate issues in the background.